Chemotherapy, IL-12 gene therapy and combined adjuvant therapy of HPV 16-associated MHC class I-proficient and -deficient tumours - Indrová, Marie; Bieblová, Jana; Jandlová, Tána; Vonka, Vladimír; Pajtasz-Piasecka, Elzbieta; Reinis, Milan (International journal of oncology, 2006)
Moderately immunogenic HPV 16-associated murine tumour cell line mimicking human HPV 16-associated neoplasms TC-1 (MHC class I(+)) and its variants, TC-1/P3C10 and TC-1/A9, with a marked down-regulation of MHC I molecules, were used to examine the effect of local interleukin 12 (IL-12) gene therapy for the treatment of early tumour transplants and minimal residual tumour disease obtained after cytoreductive chemotherapy (CMRTD). Experiments were designed to examine whether down-regulation of MHC class I molecules plays a role during chemotherapy and gene therapy of early tumour transplants. It was found that peritumoral administration of IL-12-producing tumour cell vaccines (single dose, day 8 after tumour cell administration) inhibited the growth of both TC-1 (MHC class I positive) tumours and their MHC class I-deficient variants. To investigate the antitumour effects in a clinically relevant setting, IL-12 gene therapy was utilised for the treatment of minimal residual tumour disease after cytoreductive chemotherapy. Intra-peritoneal treatment of tumour-bearing mice with ifosfamide derivative, CBM-4A, produced a significant tumour-inhibitory effect. This treatment was followed by peritumoral s.c. administration of genetically modified TC-1 (MHC class I positive) or MK16/I/IIIABC (MHC class I negative) vaccines producing IL-12 (single dose, day 7 after chemotherapy) or with recombinant interleukin 12 (rIL-12) in two cycles of 5 daily doses (days 8-19) after chemotherapy. This combined therapy significantly inhibited the growth of TC-1 and TC-1/A9 (MHC class I-) tumours. When the combined therapy of TC-1 (MHC class I positive) tumours was followed by peritumoral administration of bone marrow dendritic cell (BMDC) vaccines, the IL-12-mediated inhibitory effect was significantly boosted. In the next set of experiments, the impacts of chemotherapy and IL-12 adjuvant therapy on MHC class I surface expression were assessed. Chemotherapy and gene therapy of tumours led to the up-regulation of MHC I expression on MHC class I-deficient tumours (TC-1/A9 and TC-1/P3C10) and to down-regulation on MHC I-proficient tumours (TC-1). These findings indicate that the MHC I phenotype is not stable during tumour progression and treatment. Collectively, these results illustrate the efficacy of IL-12 gene therapy in combination with chemotherapy on HPV-associated tumours regardless of the level of MHC class I expression on the tumour cells.
Keywords: reziduální nádor; Ifosfamide; Up-Regulation; Genetic Therapy; Genes, MHC Class I; interleukin-12; HLA Antigens; upregulace; experimentální nádory; down regulace; Disease Models, Animal; Human papillomavirus 16; Neoplasm, Residual; Cancer Vaccines; mužské pohlaví; geny MHC třídy I; genetická terapie; Interleukin-12; Mice; Tumor Cells, Cultured; Down-Regulation; ifosfamid; modely nemocí na zvířatech; HLA antigeny; imunoterapie; zvířata; Humans; Neoplasms, Experimental; myši; Immunotherapy; lidský papilomavirus 16; nádorové buňky kultivované; protinádorové vakcíny; lidé; Male; Animals